The role of domestic law in determining deductibility of interest : from arm’s length principle to comprehensive interest barriers - Jawa, Joana Sara Akram (2022)
In corporate income tax there is a fundamentally different tax treatment of equity investments and loan financing. The problem dealt with in this master thesis stems from the rule that interest is deductible in computing the taxable income, unless the interest is caught by thin capitalization rules or other anti-abuse provisions. In an international context, from a tax point of view, it may be more advantageous to arrange fund for a company by ways of loan rather than resorting to an equity contribution. Multinational groups can take advantage of this contrast and plan their worldwide leverage to minimize their overall tax liability. Following the increasing awareness of national tax authorities and international institutions on this subject, this has led international institutions to recommend the introduction of new rules referred in this study as “Comprehensive Interest Barriers”. This master dissertation study hasthe purpose to assess Comprehensive Interest Barriers in light of Article 9 OECD Model Convention. In literature, there has been conflicting ideas regarding the interaction of these rules with the OECD Model Convention, particularly with Article 9. Within this context, the OECD released a public discussion draft, which contains proposed amendments on the commentaries of Article 9 in order to clarify its application. This study will demonstrate how, with the proposed amendments, the OECD is able to restore the certainty in the international playing field. On the basis of this conclusion, this study will come up with a potential “price to pay” for that said certainty and all the consequences attached to it.